Territories of Extraction: Mapping Palimpsests of Appropriation - Morata, Berta; Cavalieri, Chiara; Rizzo, Agatino; Luciani, Andrea (Urban Planning, 2020)
This article—framed as a methodological contribution and at the intersection between the critical urban, urban political ecology and world-ecology disciplines—builds on Corboz’s metaphor of ‘territory as a palimpsest’ to explore the representation of the socio-economic and ecological processes underpinning uneven development under extractive capitalist urbanization. While the palimpsest approach has typically been used to map transformations of more traditional urban morphologies, this work focuses instead on remote extraction territories appropriated by the global economy and integral to planetary urbanization. The article suggests the central notion of ‘palimpsests of appropriation’ as a lens to map the extraction processes. It does so in its multi-scalar and temporal dimensions and on the basis of the three intertwined frames—i.e., the productive, distribution and mediation palimpsest—shortly exemplifying its use on the ground for the iron ore extraction territory in the Swedish-Norwegian Arctic. With this, the article contributes to the development of an expanded representational methodology and conception of territories of extraction—where social and natural production are brought together—illustrating how appropriation has been (re)shaping each of the frames throughout historical thresholds, but also how socio-natures are being (re)made in its image.